Frontiers of history : historical inquiry in the twentieth century - Kelley, Donald R., 1931- (Yale University Press, 2006)
This book, the third volume of Donald Kelley's monumental survey of Western historiography, covers the twentieth century, especially Europe. As in the first two volumes, the author discusses historical methods and ideas of all sorts to provide a detailed map of historical learning. Here he carries the survey forward to our own times, confronting directly the challenges of postmodernism and historical narrative. Kelley offers highly original discussions of historians of the last half century (including friends and mentors), the 'linguistic turn', the 'end of history', the philosophy of history, and various new methods of histories. The book focuses first on the state of the art of history in France, Germany, Britain, and the United States on the eve of World War I. Kelley then traces every important historiographical issue and development historians have encountered in the twentieth century. With the completion of this trilogy, Kelley presents the only comprehensive modern survey of historical writing. He provides an unparalleled portrait of the rich variety of historical method along with an insider's view of the challenges of capturing history on the written page.